Analisa Spasial Berbasis GIS (Geographic Information System) Hubungan Struktur Geologi dengan Keberadaan Urat Epitermal di Tambang Emas Pongkor, Kabupaten Bogor, Provinsi Jawa Barat - , NURUL HIDAYATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Pongkor is the largest epithermal gold mining located in Bogor Regency, West Java, Indonesia operated by PT. Aneka Tambang Tbk. Pongkor has four primary veins which parallel in Northwest - Southeast relative direction. It is dominantly found in extensional fractures or faults which also in the same direction. Nowadays the exploration activity is still ongoing with multidiscipline approach. Nevertheless, quantitative interpretation has never been applied in the research area. As science growing faster, researcher want to explore the area with another method based on GIS (Geographic Information System) (hereinafter named GIS). One of these GIS methods is spatial analysis, which used to knowing spatial relationship between the occurrence of epithermal veins regarding the control of geologic aspects, especially structures (or lineaments). Interpretation of geologic structures (lineaments) is based on DEM image, which generated from digital topographic map. This image is enhanced using one of GIS tools in order to get good visual for better interpretation. Lineaments are buffered and dissolved by direction in several distance. After those spatial analyses were done, field measurements data (such as lithologic sample, structures and veins measurements) are used to verify the result of spatial analysis. The result is a map where shows the location of potential veins predicted inside Pongkor contract area. It could be one of the guidance for development evaluation in Pongkor